RIWAYAT ASI EKSKLUSIF DAN STUNTING PADA ANAK USIA 24-59 BULAN DI KECAMATAN PAJANGAN DAN PLERET, KABUPATEN BANTUL - Indah Suwartini; Febrina Suci Hati; Bunga Astria Paramashanti (Jurusan Gizi Poltekkes Kemenkes Makassar, 2020)
Stunting prevalence among Indonesian children remained high (30,8%). Existing studies found varied results on the association between exclusive breastfeeding and stunting. This study aimed to analyze whether exclusive breastfeeding was a risk factor for stunting among children aged 24-59 months in Pajangan and Pleret Subdistricts, Bantul District. A case-control study design was conducted. As many as 43 cases and 43 controls were selected using multistage cluster sampling. Cases were children with stunting status while controls were non-stunted children. Independent variable was history of exclusive breastfeeding whereas dependent variable was stunting. Statistical analyses performed in this study included descriptive statistics and chi-square test. No significant relationship between history of exclusive breastfeeding and stunting among children aged 24-59 months in Pajangan and Pleret Subdistricts, Bantul District. Nonetheless, the proportion of children receiving exclusive breastfeeding was higher among non-stunted children (81%) compared to the proportion of children receiving exclusive breastfeeding among stunted children (65%). Exclusive breastfeeding was not a risk factor for stunting among children aged 24-59 months.